2014
DOI: 10.1002/cncr.28895
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive radiofrequency treatment effect on mitochondria in pancreatic cancer cells

Abstract: Background Development of novel therapeutic approaches for cancer therapy is important, especially for tumors that have poor response or develop resistance to standard chemotherapy and radiation. We discovered that non-invasive radiofrequency (RF) fields can affect cancer, but not normal cells, inhibit progression of tumors in mice, and enhance anticancer effect of chemotherapy. However, it remains unclear what physiological and molecular mechanisms this treatment induces inside cells. Here, we studied the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Duration of RF-EF exposure has been reported as an important factor in results of cell studies. Curley et al reported that RF-EF exposure could cause mitochondrial damage and induce autophagy in in-vitro studies [51]. Treatment with PEG-GNRs caused significant cell death when exposed to RF-EF.…”
Section: Resultsmentioning
confidence: 99%
“…Duration of RF-EF exposure has been reported as an important factor in results of cell studies. Curley et al reported that RF-EF exposure could cause mitochondrial damage and induce autophagy in in-vitro studies [51]. Treatment with PEG-GNRs caused significant cell death when exposed to RF-EF.…”
Section: Resultsmentioning
confidence: 99%
“…This possibly contributes to a higher treatment specificity for tumour tissue, also at the cellular level [10]. Intriguingly, RF might also induce a temperature-independent effect on cell drug permeability and metabolism [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The cartridge with cells was placed into a Seahorse Analyzer incubator unit for 60 min before running a program for equilibration. The basal rates of oxygen consumption were measured three times during the first 15 min, and oligomycin (50 μM), carbonyl cyanide- p -trifluoromethoxy-phenylhydrazone (FCCP) (50 μM), and a mixture of anti-mycin A and rotenone (25 μM) were subsequently added to the cells, followed by three measurements for each statement [ 63 ].…”
Section: Methodsmentioning
confidence: 99%